STUDI TENTANG KEGIATAN EKSTRAKURIKULER SISWA DI MAN KOTO BERAPAK KECAMATAN BAYANG KABUPATEN PESISIR SELATAN - -, Meldawati - (STKIP PGRI Sumbar, 2014)
This study aimed to obtain information from Ekstrakurikulwr Activity Studies Students In MAN Koto Berapak District of Bayang South Coastal District include: Implementation of extracurricular activities from the early onset of established until now, support the school to extracurricular activities, the impact of extracurricular activities for students. This research is qualitative. The information in this study there are two, key informants are students who take the extra, ordinary informants are students who do not follow the extracurricular, teachers, and local communities. Determination technique of information by researchers is by interview. The results of the field study as follows: a) The current implementation runs smoothly extracurricular school before it runs less smoothly. Extracurricular activities carried out almost every day of the week, extracurricular MAN is in quite a lot but only bebarapa are active. While extracurricular activities of students who take more than a portion of the total number of students in schools with a coach that is one to three people from each type of activity. Students never enter the race out of the region, except of extracurricular scout. b) support school extracurricular activities proved that the furnishing of equipment, although not all equipment complete activities. However, the response of the school there is less support when the invitation to participate in extracurricular race out of the area. The school rarely ask extracurricular development and the school also does not provide a special place for each extracurricular activity. c) extracurricular positive impact on students. There is no active influence on ekatrakurikuler with learning achievement, parents, and students who do not follow the organization. Allowance will be increased by the parents of students in accordance with the current requirements following the activity, students active in extracurricular closer to the teacher at school than other students.